Hypovitaminosis D: Prevalence, Determinants and its Association with Asthma in Adolescents in Cyprus - Kolokotroni, Ourania (Faculty of Health Sciences, Department of Nursing, Cyprus University of Technology, 2015)
Background: Hypovitaminosis D is becoming an important public health problem worldwide. Despite the limited number of studies in children and adolescents and the lack of data from large parts of the world, hypovitaminosis D seems to be affecting individuals across all age groups and people in all geographical regions, even in areas with abundant sun throughout the year. The main determinants of a lower vitamin D status pertain to factors associated with synthesis, intake and/or bioavailability of vitamin D whilst others are still under investigation. For example lower vitamin D levels have been widely reported among obese individuals but evidence on the association of vitamin D with adiposity measures beyond the obese status and across the BMI range is limited. The role of vitamin D in skeletal disease is well known and recognized. Emerging evidence, however, suggests that vitamin D might be implicated in the pathophysiology of several chronic diseases, including asthma and allergies. Objectives: The aims of this study were (a) to describe the distribution of vitamin D levels and estimate the prevalence of compromised D status (severe deficiency, deficiency and insufficiency) among healthy (non-asthmatic) adolescents in Cyprus, (b) to explore the determinants of lower vitamin D levels and compromised vitamin D status, including measures of adiposity, (c) to assess the magnitude of difference if any in vitamin D levels and status between healthy (non asthmatic) adolescents and adolescents with current wheezing and/or asthma and (d) to investigate the association between vitamin D levels or status with lung function, allergic sensitization and other allergic conditions as well as asthma severity among asthmatics. Methods: Using a case-control approach, participants were selected from a cohort of 5384 16-17 year old adolescents who completed the ISAAC questionnaire. Those who reported wheezing in the past 12 months were eligible to participate and further grouped into active asthmatics (CWA), if also reporting a diagnosis of asthma, and current wheezers only (CWO). The healthy controls were sampled amongst Never Wheezers/ Never Asthmatics (NWNA). All participants had serum levels of 25(OH)D measured between Nov 2007 and May 2008 and underwent assessment of body composition, diet, skin type, physical activity and sun exposure. Information was also collected on socio-demographic characteristics. In order to estimate the prevalence of hypovitaminosis, Vitamin D status was classified as (a) severe deficiency (serum 25-hydroxy-vitamin D levels < 12 ng/mL), deficiency (levels 12- 20 ng/mL), insufficiency (levels 20-30 ng/mL) and sufficiency (levels ≥ 30 ng/mL). The association of vitamin D levels and status with potential predictors, including sex standardized z-scores of BMI and BF%, was investigated in linear and logistic regression models respectively. Differences in levels of 25(OH)D and vitamin D status between the three study groups were investigated in multivariable linear regression models and logistic (binary and ordinal) regression models before and after adjusting for potential confounders, including seasonality. Similarly, the association of vitamin D with other respiratory and allergy outcomes in all study groups as well as asthma severity indicators among asthmatics was investigated in regression models after adjusting for important confounders. Results: A total of 69 CWA, 121 CWO and 671 NWNA participated in the study (71% overall response rate). Amongst NWNA, only one in ten children had sufficient levels of vitamin D (≥30 ng/ml) while prevalence of vitamin D deficiency (12-20 ng/ml) and severe deficiency (<12 ng/ml) were 31.7% and 4.0% respectively. Lower vitamin D was associated with winter and spring season, female gender, reduced sun exposure in winter and darker skin type. Participants with highest BMI and BF% had increased adjusted odds of vitamin D insufficiency compared to a middle reference group i.e. OR 3.00 (95% CI 1.21, 7.45) and OR 5.02 (95% CI 1.80, 13.97) respectively. Similarly, the odds of vitamin D insufficiency were higher for participants in the lowest BMI (OR 4.92, 95% CI 1.21, 20.08) and BF% (OR 4.48, 95% CI 1.47, 13.62) groups, suggesting a U shape association of adiposity with compromised vitamin D status. Unadjusted mean serum levels of 25(OH)D were 22.90 (SD 6.41), 23.96 (SD 6.32)and 21.15 (SD 5.59) ng/mL in NWNA, CW0, CWA respectively (p=0.014). Even after adjusting for potential confounders, mean vitamin D levels were significantly lower amongst CWA compared to both NWNA (adjusted beta -1.67, 95% CI= -3.20, -0.14, p=0.03) and CWO (adjusted beta -2.60, 95% CI= -4.43, -0.77, p=0.01). Severe (<12 ng/mL), moderate (<25 ng/mL) or insufficient (<30 ng/mL) vitamin D status was more prevalent among CWA, who were 1.6 times (95% CI 1.01, 2.53) more likely to belong to a lower vitamin D category compared to NWNA. Within CWA, there was a negative trend between vitamin D levels and the number of reported asthma severity indicators Vitamin D levels were not shown to be associated with lung function measures either in the non-asthmatic or asthmatic populations. In contrast, there was some evidence to suggest that allergic sensitization, and more importantly polysensitization, was more prevalent in individuals with a compromised vitamin D status amongst current wheezers (CWO & CWA). Specifically, current wheezers with vitamin D insufficiency compared to those with sufficient levels of vitamin D were almost 4-times more likely to be sensitized to at least one allergen (OR 3.83, 95% CI 1.23, 11.96). Finally, allergic rhinitis in NWNA appears to be less prevalent in adolescents with vitamin D deficiency whereas it appears more prevalent amongst vitamin D deficient Current Wheezers. With regards to the association between vitamin D and eczema, no safe conclusions could be drawn. Conclusions: This is the first study to investigate vitamin D deficiency among adolescents in Cyprus while no data are currently available for any other population group. The study provides further evidence that hypovitaminosis D is becoming an important public health problem internationally, at least during the winter months even in countries with abundant sunlight. Furthermore, the study findings add to emerging evidence in the literature that hypovitaminosis D might be implicated in asthma and allergy disease development, or at least severity. As currently most evidence comes from cross-sectional studies, more studies especially of a longitudinal design are needed to investigate the asthma-vitamin D association since a number of unanswered questions remain including the critical time frame and optimal vitamin D levels required to prevent the development of asthma and allergies. Such information will inform the design of randomized control trials of vitamin D supplementation, which in turn will provide important evidence whether the association is causal and reversible. Finally, more studies are needed to assess vitamin D levels in the general population of Cyprus as well as worldwide, identify vulnerable groups and develop region-specific measures to improve vitamin D status. Improving vitamin D status in any population will reduce the risk of recognized musculoskeletal problems associated with vitamin D deficiency and it might reduce morbidity and mortality from a number of other chronic conditions should emerging evidence on their association with vitamin D proves to be causal.
Keywords: Determinants of vitamin D deficiency; Adolescents; Vitamin D; Asthma; Allergies; Body Mass Index; Body fat Percent; Asthma severity; Allergic sensitization; Lung function